Evaluation of Polygenic Risk Scores for Prediction of Prostate Cancer in Korean Men - Oh, Jong Jin; Kim, Eunae; Woo, Eunjin; Song, Sang Hun; Kim, Jung Kwon; Lee, Hakmin; Lee, Sangchul; Hong, Sung Kyu; Byun, Seok-Soo (Frontiers in Oncology, 2020)
Aims : The purpose of this study is to evaluate an aggregate influence of prostate cancer (PCa) susceptibility variants on the development of PCa in Korean men by using polygenic risk score (PRS) approach. Methods : An analysis of 1,001 cases of PCa and 2,641 controls was performed to: i) identify potential PCa-related risk loci in Koreans and ii) validate the cumulative association between these loci and PCa using PRS. Subgroup analyses based on risk stratification were conducted to better characterize the potential correlation to key PCa-related clinical outcomes (e.g., Gleason score, prostate specific antigen levels). The results were replicated using 514 cases of PCa and 548 controls from an independent cohort. Results : Genome-wide association analysis from our discovery cohort revealed 11 candidate SNPs associated with PCa showing statistical significance of p<5.0×10-5. Seven variants were located at 8q24.21 (rs1016343, rs16901979 and rs13252298 in PRNCR1; rs4242384, rs7837688, and rs1447295 in CASC8; rs1512268 in NKX3). Two variants located within HNF1B (rs7501939 and rs4430796) had a significant negative association with PCa risk (OR=0.717 and 0.747, p=6.42×10-7 and 3.67×10-6, respectively). Of the six independent SNPs that remained after linkage disequilibrium (LD) pruning, the top four SNPs best predicted PCa risk with an AUC of 0.635 (95% CI: 0.58-0.69). Those with top 25% polygenic risk had a 4.18-fold increased risk of developing PCa compared with those with low risk. Conclusions : 11 PCa-risk variants in Korean men were identified; PRSs of a subset of these variants could help predict PCa susceptibility.